ASSESSING PUBLIC SECTOR EFFICIENCY IN DEVELOPING COUNTRIES WITH DEA AND BOOTSTRAP ANALYSIS - Nahed Trabelsi; Younes Boujelbene (Journal of Smart Economic Growth, 2023)
The purpose of this paper is to analyse public sector efficiency of 75 developing countries. In a first step, we have computed Public Sector Performance (PSP) indicators for the period of 2000-2018. Based on these PSPs, we have estimated efficiency scores using Data Envelopment Analysis (DEA). The input-oriented DEA analysis reveals that countries can achieve the same level of performance using 42% less spending. The output-oriented DEA models conclude that developing countries can increase their performance by 33% with the same level of public spending. In a second step, we have examined the determinants of efficiency of public sector by applying a Bootstrap analysis. The empirical explanation of the efficiency scores reveals that the strong institutions can play a crucial role in enhancing the efficiency of public sector. Our findings can be useful for policymakers in order to set out a structural adjustment plan to improve the efficiency level for public sector.